VARIABILITY AND ASSOCIATION OF AGRONOMIC CHARACTERS IN MUNGBEAN - R. S. PAN; ,A. K. SINGH; S. KUMAR (The Bioscan, 2014)
In nine genotypes of mungbean, the maximum extent of genetic variability was exhibited by100-seed weight followed by number of pods/plant. These two characters indicating the possibility of their improvement through individual plant selection also recorded high heritability coupled with high genetic advance. The grain yield was positively correlated with pod length, number of seeds/pod and number of pods/plant which could be considered as important selection criteria in improvement of grain yield of mungbean. The genotypes K-851 (2.49 t/ha), HARSHA (2.42 t/ha) and VC 6368 (46-40-4)(2.40 t/ha) were found promising in respect of grain yield and could be considered promising for rainy season cultivation in Eastern Plateau and Hill Region of India.